“Wait anaphase” signals are not confined to the mitotic spindle - Heasley, Lydia R.; Markus, Steven M.; DeLuca, Jennifer G. (Molecular biology of the cell, 2017)
The spindle assembly checkpoint ensures the faithful inheritance of chromosomes by arresting mitotic progression in the presence of kinetochores that are not attached to spindle microtubules. This is achieved through inhibition of the anaphase-promoting complex/cyclosome by a kinetochore-derived “wait anaphase” signal known as the mitotic checkpoint complex. It remains unclear whether the localization and activity of these inhibitory complexes are restricted to the mitotic spindle compartment or are diffusible throughout the cytoplasm. Here we report that “wait anaphase” signals are indeed able to diffuse outside the confines of the mitotic spindle compartment. Using a cell fusion approach to generate multinucleate cells, we investigate the effects of checkpoint signals derived from one spindle compartment on a neighboring spindle compartment. We find that spindle compartments in close proximity wait for one another to align all chromosomes before entering anaphase synchronously. Synchrony is disrupted in cells with increased interspindle distances and cellular constrictions between spindle compartments. In addition, when mitotic cells are fused with interphase cells, “wait anaphase” signals are diluted, resulting in premature mitotic exit. Overall our studies reveal that anaphase inhibitors are diffusible and active outside the confines of the mitotic spindle from which they are derived.